Development of a novel Ara h 2 hypoallergen with no IgE binding or anaphylactogenic activity - Tscheppe, Angelika (J Allergy Clin Immunol, 2020)
BACKGROUND: To date, no safe allergen-specific immunotherapy for patients with peanut allergy is available. Previous trials were associated with severe side effects. OBJECTIVE: We sought to determine the relative importance of conformational and linear IgE-binding epitopes of the major peanut allergen Ara h 2 and to produce a hypoallergenic variant with abolished anaphylactogenic activity. METHODS: Wild-type Ara h 2 and a mutant lacking the loops containing linear IgE epitopes were produced in insect cells. Conformational IgE epitopes were removed by unfolding these proteins through reduction and alkylation. IgE binding was tested by means of ELISA with sera from 48 Ara h 2–sensitized patients with peanut allergy. Basophil activation and T-cell proliferation were tested with blood samples from selected patients. Anaphylactogenic potency was tested by using intraperitoneal challenge of mice sensitized intragastrically to peanut extract. RESULTS: Patients’ IgE recognized conformational and linear epitopes in a patient-specific manner. The unfolded mutant lacking both types of epitopes displayed significantly lower IgE binding (median ELISA OD, 0.03; interquartile range, 0.01-0.06) than natural Ara h 2 (median ELISA OD, 0.99; interquartile range, 0.90-1.03; P < .01). Basophil activation by unfolded mutant Ara h 2 was low (median area under the curve, 72 vs 138 for native wild-type Ara h 2; P < .05), but its ability to induce T-cell proliferation was retained. Unfolded mutants without conformational epitopes did not induce anaphylaxis in peanut-sensitized mice. CONCLUSIONS: By removing conformational and linear IgE epitopes, a hypoallergenic Ara h 2 mutant with abolished IgE binding and anaphylactogenic potency but retained T-cell activation was generated.